GENDER SEGREGATION IN SOCIAL SCIENCE LEARNING AS AN EFFORT TO IMPROVE THE QUALITY OF LEARNING FOR CLASS VII STUDENTS AT MTS DAARUL AMANAH, RAJAGALUH DISTRICT, MAJALENGKA REGENCY - Anton Rudiono (Jurnal Kajian Gender dan Anak, 2022)
SEGREGASI GENDER DALAM PEMBELAJARAN IPS SEBAGAI UPAYA MENINGKAT KAN KUALITAS BELAJAR SISWA KELAS VII DI MTS DAARUL AMANAH KECAMATAN RAJAGALUH KABUPATEN MAJALENGKA